Критерий эффективности тепловых насосов с учетом группового влияния аргументов - Капустенко, Пётр Алексеевич; Илюнин, О. О.; Болдырев, Станислав Александрович; Гарев, Андрей Олегович; Лещенко, Е. В.; Перевертайленко, Александр Юрьевич; Селяков, А. М.; Шамраев, А. А. (НТУ "ХПИ", 2013)
Наведено методику оцінки повноти обліку факторів при синтезі критерію економічної ефективності теплових насосів. Запропоновано підхід перехресного аналізу і кластеризації факторів, що різним чином впливають на ефективність технічних систем. Зазначено, що запропонований підхід підвищує чутливість критеріїв і придатний для оцінки адекватності математичних моделей об'єктів.

The method of accounting factors in completeness evaluation for the synthesis of the economic efficiency criterion of heat pumps is considered. An approach of a cross-analysis and the factors influencing to the effectiveness of the technical systems clustering is proposed. It was noted that the proposed method increases the sensitivity criteria and is suitable for the assessment of the mathematical objects models’ adequacy.
The criterion of efficiency of heat pumps with a view of group influence of the arguments
Keywords: низкопотенциальные источники тепла; ТН; сложная техническая схема; исходные данные; комплексная тепловая установка